Rural Tourism as a Development Strategy in Low-Density Areas: Case Study in Northern Extremadura (Spain) - Ana Nieto Masot (Sustainability, 2021)
The appearance of new trends and models of tourism consumption has allowed the proliferation of rural tourist facilities in northern Extremadura. This article analyzes the economic, social, and heritage (natural and cultural) variables to relate them to the tourism offer and demand in these areas. The present study used geostatistical techniques such as Principal Component Analysis (PCA) and their spatial location through Geographic Information Systems (GIS) to determine the distribution and degree of incidence of these variables in the territories. The results obtained confirm the existence of imbalances in the tourism sector, which made it possible to determine which tourist territories have implemented the best lines of action to receive visitors, increase economic income, and preserve the population in rural areas with deficiencies in their tourism development.